Indonesian Nursing Diagnosis Standards for COVID-19 in Patients in East Java, Indonesia - Susanto, Joko; Ilkafah, Ilkafah; Tyas, Anestasia Pangestu Mei; Makhfudli, Makhfudli; Yusuf, Ah. (Fakultas Ilmu-ilmu Kesehatan, 2025)
Establishing the correct nursing diagnosis in patients with COVID-19 is crucial for determining the most effective nursing care to help patients recover optimally. The research aims to describe and analyze nursing diagnoses in COVID-19 patients treated in isolation rooms and Intensive Care Units (ICUs). This research used secondary data analysis from 296 hospital medical records of COVID-19 patients at dr. Soegiri Lamongan Hospital from February to August 2021. The researchers employed a simple random sampling technique to collect the data and analyzed it using descriptive statistics. The research revealed that the common symptoms and nursing diagnoses among hospitalized COVID-19 patients included hyperthermia, coughing, shortness of breath, decreased consciousness, ineffective airway clearance, impaired gas exchange, self-care deficit, impaired spontaneous ventilation, spontaneous circulatory disorders, knowledge deficit, and shock risk. The results of this study provide information about variations in nursing diagnoses among COVID-19 patients. Thus, nurses can use this primary data to develop comprehensive standards of nursing care for COVID-19 patients.